소복재정맥에서 발생한 혈전을 동반한 여러 개의 정맥류 - 강찬; 송재황; 원유건; 이기수; Chan Kang; Jae-Hwang Song; Yougun Won; Eric W. Tan; Gi-Soo Lee (대한족부족관절학회지, 2024)
Several types of soft tissue masses occur in the lower extremities. A mass associated with blood vessels is often difficult to diagnose. A 15-year-old male patient visited the author's hospital with discomfort and edema in his right calf that had persisted for six months. A physical examination showed no palpable mass other than mild edema. Three masses were found during the ultrasound scan along the small saphenous vein. The masses had a cyst-like appearance and were filled with thrombus. In duplex ultrasound, vascular reflux was represented inside the masses. During surgery, it was suspected that vascular deformation occurred in the small saphenous vein, and simple ligation and resection treatments were performed. The patient was finally diagnosed with venous aneurysms accompanied by thrombosis based on the histology tests. The symptoms disappeared after surgery, and there were no recurrences or unusual findings at the follow-up one year later. Venous aneurysms occurring in the superficial veins of the lower extremities are rarely reported, but treatment and diagnosis are important. This paper reports a case of an aneurysm on the small saphenous vein.